2017
DOI: 10.4049/jimmunol.1601563
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Low-Density Lipoprotein Immune Complex Priming of the Nlrp3 Inflammasome Involves TLR and FcγR Cooperation and Is Dependent on CARD9

Abstract: Oxidized LDL (oxLDL) is known to activate inflammatory responses in a variety of cells, especially macrophages and dendritic cells (DCs). Interestingly, much of the oxLDL in circulation is complexed to antibodies and these resulting immune complexes (ICs) are a prominent feature of chronic inflammatory disease such as atherosclerosis, Type-2 diabetes, systemic lupus erythematosus and rheumatoid arthritis. Levels of oxLDL-ICs often correlate with disease severity, and past studies have demonstrated that oxLDL-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
62
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 48 publications
0
62
0
2
Order By: Relevance
“…Intriguingly, this analysis revealed that oxLDL-induced trained immunity was influenced by several independent genetic polymorphisms in the putative regulatory region of PYCARD, the gene encoding the principal inflammasome adaptor protein ASC, and also in the gene for the endogenous IL-1 inhibitory molecule IL-1RAP. Together with a large array of studies linking NLRP3 to the inflammatory response in metabolic diseases (Duewell et al, 2010; Rhoads et al, 2017; Sheedy et al, 2013), this provided evidence for a potential key role of the NLRP3 inflammasome pathway in the induction of trained immunity under conditions of WD feeding. Strongly supporting this hypothesis, we observed an almost complete protection from WD-induced changes in systemic inflammation, induction of hematopoiesis and functional and transcriptomic reprogramming of GMPs isolated from Ldlr −/− /NLRP3 −/− mice.…”
Section: Discussionmentioning
confidence: 84%
“…Intriguingly, this analysis revealed that oxLDL-induced trained immunity was influenced by several independent genetic polymorphisms in the putative regulatory region of PYCARD, the gene encoding the principal inflammasome adaptor protein ASC, and also in the gene for the endogenous IL-1 inhibitory molecule IL-1RAP. Together with a large array of studies linking NLRP3 to the inflammatory response in metabolic diseases (Duewell et al, 2010; Rhoads et al, 2017; Sheedy et al, 2013), this provided evidence for a potential key role of the NLRP3 inflammasome pathway in the induction of trained immunity under conditions of WD feeding. Strongly supporting this hypothesis, we observed an almost complete protection from WD-induced changes in systemic inflammation, induction of hematopoiesis and functional and transcriptomic reprogramming of GMPs isolated from Ldlr −/− /NLRP3 −/− mice.…”
Section: Discussionmentioning
confidence: 84%
“…26 In recent years, numerous studies have confirmed that NLRP3 inflammasomes can be activated by two abundant components of atherosclerotic plaque (ox-LDLs and crystalline cholesterol). 26,[47][48][49] Hoseini et al reported that high numbers of inflammasomes were present in atherosclerotic plaque and ox-LDL-induced cells in vitro. 26 However, the mechanism by which inflammasomes function in atherosclerosis is complex, and involves several signaling pathways, including the JNK-1 and ASK1 pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, oxLDL-ICs have only recently been implicated in disease pathogenesis. OxLDL-ICs were found to be more potent primers of the NLRP3 inflammasome and elicited greater IL-1β production than free oxLDL in bone marrow-derived dendritic cells (DCs) [4]. However, the mechanism behind oxLDL-ICs enhanced inflammatory effects is unknown.…”
mentioning
confidence: 99%
“…FcγRs are found on antigen presenting cells (APCs) such as macrophages, DCs, and B-cells and have high affinity for the Fc region of IgG antibodies. In vitro studies demonstrate that oxLDL-ICs can signal through Fc receptors in both human macrophage cells lines and murine bone marrow-derived DCs, likely in concert with toll-like receptor 4 and the scavenger receptor CD36 [4,5]. FcγRs can be either activating or inhibitory, containing an immunoreceptor tyrosine-based activation motif or an immunoreceptor tyrosine inhibitory motif, respectively [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation